2000
DOI: 10.1104/pp.124.3.1105
|View full text |Cite
|
Sign up to set email alerts
|

A Genomics Approach to the Comprehensive Analysis of the Glutathione S-Transferase Gene Family in Soybean and Maize

Abstract: By BLAST searching a large expressed sequence tag database for glutathione S-transferase (GST) sequences we have identified 25 soybean (Glycine max) and 42 maize (Zea mays) clones and obtained accurate full-length GST sequences. These clones probably represent the majority of members of the GST multigene family in these species. Plant GSTs are divided according to sequence similarity into three categories: types I, II, and III. Among these GSTs only the active site serine, as well as another serine and arginin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
266
0
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(291 citation statements)
references
References 62 publications
9
266
0
16
Order By: Relevance
“…Fragments of the ORFs (gstI and gstIIIb), or fragments containing 3Ј UTRs joined to the 3Ј ends of the ORF (apx, StUCP, and TaUCP), were obtained by reverse transcriptase-mediated PCR with total RNA from normal maize seedlings as a template and were cloned into pGEMT-Easy. Although GSTI and GSTIIIb proteins are homologous (50% identity) and belong to the same family of maize GSTs (type I; McGonigle et al, 2000), there was no nucleotide homology detected for the gstI and gstIII PCR fragments used for analysis.…”
Section: Other Hybridization Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragments of the ORFs (gstI and gstIIIb), or fragments containing 3Ј UTRs joined to the 3Ј ends of the ORF (apx, StUCP, and TaUCP), were obtained by reverse transcriptase-mediated PCR with total RNA from normal maize seedlings as a template and were cloned into pGEMT-Easy. Although GSTI and GSTIIIb proteins are homologous (50% identity) and belong to the same family of maize GSTs (type I; McGonigle et al, 2000), there was no nucleotide homology detected for the gstI and gstIII PCR fragments used for analysis.…”
Section: Other Hybridization Probesmentioning
confidence: 99%
“…Maize orthologs of cytosolic glutathione S-transferases type I (gstI and gstIIIb; McGonigle et al, 2000) and ascorbate peroxidase (apx; Shigeoka et al, 2002) were chosen for analysis (Table 1). The maize gstIIIb and apx genes are related closely to Arabidopsis and tobacco genes that serve as markers for the oxidative burst response (Alvarez et al, 1998;Mittler et al, 1999).…”
Section: Analysis Of Oxidative Stress In Ncs Mutantsmentioning
confidence: 99%
“…55 GSTs in Arabidopsis thaliana (Dixon et al 2009), 82 in Oryza sativa , 81 in Populus (Lan et al 2009), 42 in maize (McGonigle et al 2000), 65 in broccoli (Vijayakumar et al 2016), 84 in Hordeum vulgare (Rezaei et al 2013), 20 in Draceana cambodiana (Zhu et al 2016), and 37 GSTs in Physcomitrella patens (a bryophyte) have been identified (Liu et al 2013). …”
mentioning
confidence: 99%
“…In plants, the glutathione transferases (GSTs 2 ; EC 2.5.1.18) are a superfamily of proteins with the dominant Phi (F) and Tau (U) classes having largely undefined functions in endogenous metabolism (1). This is in contrast to their relatively well studied role in catalyzing the glutathione conjugation of herbicides (2).…”
mentioning
confidence: 99%